Nursing of a patient with excessive exercise-induced rhabdomyolysis complicated by acute liver failure (1例过度运动致横纹肌溶解症并发急性肝功能衰竭患者的护理体会) - YIN Junxia (殷俊霞); HAN Yamei (韩亚妹); WANG Wencui (王文翠); LIU Mengqi (刘梦绮) (Journal of International Translational Medicine Limited, 2024)
This paper summarized the treatment and nursing of a patient with excessive exercise-induced rhabdomyolysis complicated by acute liver failure. After a comprehensive nursing assessment on medical history and illness condition, early treatment included fluid replacement, diuresis, organ function protection, and Traditional Chinese Medicine treatment by syndrome differentiation were carried out. Traditional Chinese Medicine nursing techniques such as Thunder-Fire moxibustion, auricular acupoint pressing were adopted to relieve the pain, upper limb swelling and other clinical symptoms. (本文总结1例因过度运动致横纹肌溶解伴急性肝功能衰竭患者的治疗和护理实践经验。患者入科后积极询问病史、完善相关检查和评估, 在给予补液、保护脏器功能、中药辨证施治等对症治疗的基础上, 采用雷火灸、耳穴埋豆等中医适宜技术, 同时加强健康宣教和出院指导, 患者疼痛明显改善, 上肢肿胀减轻。)